Transition from a meiotic to a somatic-like DNA damage response during the pachytene stage in mouse meiosis - Enguita-Marruedo, Andrea (PLoS Genet, 2019)
Homologous recombination (HR) is the principal mechanism of DNA repair acting during meiosis and is fundamental for the segregation of chromosomes and the increase of genetic diversity. Nevertheless, non-homologous end joining (NHEJ) mechanisms can also act during meiosis, mainly in response to exogenously-induced DNA damage in late stages of first meiotic prophase. In order to better understand the relationship between these two repair pathways, we studied the response to DNA damage during male mouse meiosis after gamma radiation. We clearly discerned two types of responses immediately after treatment. From leptotene to early pachytene, exogenous damage triggered the massive presence of γH2AX throughout the nucleus, which was associated with DNA repair mediated by HR components (DMC1 and RAD51). This early pathway finished with the sequential removal of DMC1 and RAD51 and was no longer inducible at mid pachytene. However, from mid-pachytene to diplotene, γH2AX appeared as large discrete foci. This late repair pattern was mediated initially by NHEJ, involving Ku70 and XRCC4, which were constitutively present, and 53BP1, which appeared at sites of damage soon after irradiation. Nevertheless, 24 hours after irradiation, a HR pathway involving RAD51 but not DMC1 mostly replaced NHEJ. Additionally, we observed the occurrence of synaptonemal complex bridges between bivalents, most likely representing chromosome translocation events that may involve DMC1, RAD51 or 53BP1. Our results reinforce the idea that the early “meiotic” repair pathway that acts by default at the beginning of meiosis is replaced from mid-pachytene onwards by a “somatic-like” repair pattern. This shift might be important to resolve DNA damage (either endogenous or exogenous) that could not be repaired by the early meiotic mechanisms, for instance those in the sex chromosomes, which lack a homologous chromosome to repair with. This transition represents another layer of functional changes that occur in meiotic cells during mid pachytene, in addition to epigenetic reprograming, reactivation of transcription, changes in the gene expression profile and acquisition of competence to proceed to metaphase.